ANALYSIS OF FACTORS AFFECTING CIRCULAR MIGRATION OF MIGRANT WORKERS IN KUTA SELATAN DISTRICT - Sri Mulyani Purwaningsih; Ni Luh Karmini (Adisam Publisher, 2026)
Non-permanent population mobility, also known as circular mobility, generally refers to the movement of people from one area to another without the intention of settling at the destination. The aim of this study is to analyze the simultaneous and partial effects of employment status, wages, education level, and work stress on the circular migration patterns of migrant workers in Kuta Selatan District. The subjects of this study are employment status, wages, education level, work stress, and migration patterns in Kuta Selatan District. The data analysis technique used in this study is binary logistic regression. The results of the study indicate that: 1) Employment status, wages, education level, and work stress have a simultaneous effect on the circular migration patterns of migrant workers in Kuta Selatan District. 2) Partially, wages and work stress have a positive and significant effect on the circular migration patterns of migrant workers in Kuta Selatan District. 3) Employment status significantly affects the circular migration patterns of migrant workers in Kuta Selatan District. 4) Education level does not affect the circular migration patterns of migrant workers in Kuta Selatan District.